Kegawatdaruratan Akibat Infeksi Saluran Akar dan Perawatan Gigi Sederhana pada Jemaat GPIB Silo, Cengkareng, Jakarta Barat - Faudah Amin, Meiny; Ariwibowo, Taufiq; Elline Istanto, Ie; Adhistya Putri, Dennisa; Yonathan, Dick; Hardi, Dicky; Kozali, Muliadi; Livia Riany, Nadya; Steward (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
Root canal infections and low public awareness regarding oral health care contribute to dental emergencies that may impact systemic health. This community service program aimed to enhance participants’ knowledge and skills in preventing and identifying early signs of dental emergencies caused by root canal infections through health education and basic dental treatment. The activity was conducted by residents of the Specialist Program in Conservative Dentistry, Faculty of Dentistry, Trisakti University, on June 14, 2025, at GPIB Silo Church, Cengkareng, West Jakarta, involving 75 participants from the men’s and women’s fellowship groups. The methods included interactive counseling using audio-visual media, administration of pre-test and post-test questionnaires, and provision of simple conservative dental treatments. The evaluation results demonstrated a notable increase in participants’ knowledge, as reflected in the rise of the average score from 52.92 in the pre-test to 62.08 in the post-test. Participants also showed increased awareness and proactive attitudes toward oral health maintenance. This program proved that direct educational intervention within the community effectively enhances knowledge and encourages preventive behavior regarding root canal infections. The community service activity successfully improved understanding of dental emergencies and emphasized the importance of preventive measures. It is recommended that similar programs be conducted regularly and expanded to other communities with improved audiovisual facilities to optimize educational outcomes in future implementations.